2015
DOI: 10.1117/12.2078396
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed acquisition of bidirectional texture functions for materials

Abstract: The bidirectional texture function (BTF) has proven a valuable model for the representation of complex spatiallyvarying material reflectance. Its image-based nature, however, makes material BTFs extremely cumbersome to acquire: in order to adequately sample high-frequency details, many thousands of images of a given material as seen and lit from different directions have to be obtained. Additionally, long exposure times are required to account for the wide dynamic range exhibited by the reflectance of many rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…When the distance is greater than 3 ′′ , the source could not be a non-nuclear black hole candidate (possibly a ULX, see in this respect Swartz et al 2008 for a discussion on the number of ULXs found in low mass galaxies). Note also that for sources #35 (NGC 4117) and #50 (NGC 4395), our estimate of the candidate black hole mass is a factor ≃ 10 larger (but still consistent due to the large intrinsic scatter of the fundamental plane relation) than the values derived by Woo & Urry (2002) and den Brok et al (2015), respectively, when studying the gas dynamics in the galaxies and/or using the virial assumption for the broad emission lines while determining the broadline region size from either reverberation mapping or optical luminosity.…”
Section: Candidate Massive Black Holes From the Xray/radio Fundamentasupporting
confidence: 79%
“…When the distance is greater than 3 ′′ , the source could not be a non-nuclear black hole candidate (possibly a ULX, see in this respect Swartz et al 2008 for a discussion on the number of ULXs found in low mass galaxies). Note also that for sources #35 (NGC 4117) and #50 (NGC 4395), our estimate of the candidate black hole mass is a factor ≃ 10 larger (but still consistent due to the large intrinsic scatter of the fundamental plane relation) than the values derived by Woo & Urry (2002) and den Brok et al (2015), respectively, when studying the gas dynamics in the galaxies and/or using the virial assumption for the broad emission lines while determining the broadline region size from either reverberation mapping or optical luminosity.…”
Section: Candidate Massive Black Holes From the Xray/radio Fundamentasupporting
confidence: 79%